Emergence of NDM-1- and CTX-M-3-Producing Raoultella ornithinolytica in Human Gut Microbiota - Wang, Shuang; Xu, Liuchen; Chi, Xiaohui; Li, Yan; Kou, Zengqiang; Hou, Peibin; Xie, Hengjie; Bi, Zhenwang; Zheng, Beiwen (Frontiers in Microbiology, 2019)
Raoultella ornithinolytica is an opportunistic pathogen of the Enterobacteriaceae family and has been implicated in nosocomial infections in recent years. The aim of this study was to characterize a carbapenemase-producing R. ornithinolytica isolate and three extended-spectrum β-lactamase (ESBL)-producing R. ornithinolytica isolates from stool samples of adults in a rural area of Shandong Province, China. The species were identified using matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF MS) and 16S rDNA sequence analysis. Antimicrobial susceptibility test showed that all four isolates were multidrug-resistant (MDR). The whole genome sequence (WGS) of these isolates was determined using an Illumina HiSeq platform, which revealed MDR-related genes. The S1 nuclease-pulsed-field gel electrophoresis (S1-PFGE) was used to characterize the plasmids carried by the R. ornithinolytica isolates. The blaNDM-1 and blaCTX-M-3 genes were probed using Southern blotting, which confirmed the location of both genes on the same plasmid with molecular weight of 336.5–398.4 kb. The transferability of blaNDM-1 and blaCTX-M was also confirmed by conjugation assays. Finally, BLAST analysis of both genes showed that mobile genetic elements were associated with the spread of drug resistance genes. Taken together, we report the presence of conjugative blaNDM-1 and blaCTX-M plasmids in R. ornithinolytica isolates from healthy humans, which indicate the possibility of inter-species transfer of drug resistance genes. To the best of our knowledge, this is the first study to isolate and characterize carbapenemase-producing R. ornithinolytica and ESBL-producing R. ornithinolytica isolates from healthy human hosts.